How digital economy shapes older adult care services: evidence from China - Qingyang Bian; Zihe Kong; Jiangming Kong (Frontiers in Public Health, 2025)
BackgroundIn the context of an aging society and the burgeoning development of the silver economy, enhancing older adult care services has emerged as a pivotal concern. The technological advancements and industrial shifts driven by the digital economy have provided a novel solution to this challenge. Besides, social organizations, as institutionalized networks of social relations, are important providers of social support for older adult people.MethodsDrawing on panel data from 30 provinces in China over the period from 2013 to 2023, this paper empirically investigates the impact mechanism through which the digital economy affects older adult care services.ResultsIt is found that the digital economy can enhance the quality of older adult care services, primarily by boosting innovation in older adult care-related corporations and driving the development of the older adult care industry (industrial agglomeration and increase in output value). Meanwhile, the positive impact of the digital economy on older adult care services is further strengthened by the social support provided by social organizations. Additionally, the digital economy can also facilitate the improvement of older adult care services in neighboring provinces to a certain extent through spatial spillover effects.ConclusionThe findings of this paper offer policy insights and confidence for accurately understanding the relationship between the digital economy and older adult care services, and for effectively enhancing older adult care services through the development of the digital economy and the improvement of social governance.